ANALISIS PENGARUH PENDIDIKAN, UPAH PENGALAMAN KERJA, JENIS KELAMIN DAN UMUR TERHADAP PRODUKTIVITAS TENAGA KERJA INDUSTRI SHUTLLECOCK KOTA TEGAL - Herawati, Nur; Sasana, Hadi (Diponegoro Journal of Economics, 2013)
Productivity is the ability of workers to produce output. The higher the output produced by a worker, showed higher levels of productivity workers. Tegal highest employment contained in one of the industrial sectors that affect the shuttlecock industry. However, many factors will affect labor productivity in the shuttlecock industry. Therefore, to be analyzed in this study is the effect of educational level factors, wages, work experience, gender and age of the industrial labor productivity shuttlecock Tegal.This study aimed to analyze the influence of educational variables, wages, work experience, gender and age of the industrial labor productivity shuttlecock Tegal. In this study using primary data by means of regression analysis. The samples are 67 people spread across the three largest shuttlecock industry Tegal.Results of this study indicate that the variable wages,Â work experience, gender and the number of dependents a positive influence of the industrial labor productivity shuttlecock Tegal. While the education variables do not significantly affect labor productivity in industry shuttlecock Tegal.